Review on the Recent Advances on Typhoid Vaccine Development and Challenges Ahead. (29th July 2020) - Syed, Khalid Ali; Saluja, Tarun; Cho, Heeyoun; Hsiao, Amber; Shaikh, Hanif; Wartel, T Anh; Mogasale, Vittal; Lynch, Julia; Kim, Jerome H; Excler, Jean-Louis; Sahastrabuddhe, Sushant
Abstract: Control of Salmonella enterica serovar typhi ( S. typhi), the agent of typhoid fever, continues to be a challenge in many low- and middle-income countries. The major transmission route of S . typhi is fecal-oral, through contaminated food and water; thus, the ultimate measures for typhoid fever prevention and control include the provision of safe water, improved sanitation, and hygiene. Considering the increasing evidence of the global burden of typhoid, particularly among young children, and the long-term horizon for sustained, effective water and sanitation improvements in low-income settings, a growing consensus is to emphasize preventive vaccination. This review provides an overview of the licensed typhoid vaccines and vaccine candidates under development, and the challenges ahead for introduction.